1975
DOI: 10.1084/jem.142.5.1065
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of C-reactive protein with the complement system. III. Complement-dependent passive hemolysis initiated by CRP.

Abstract: Interactions of CRP with various substrates in the presence of human serum have been shown to result in efficient activation of C components C1-C5. We now report the ability of CRP to initiate C-dependent hemolysis. For this purpose CRP was isolated by affinity chromatography using pneumococcal CPS and gel filtration; its purity was established by several criteria. Erythrocytes were coated with CPS (E-CPS) and passively sensitized with CRP. C-dependent lysis of these cells was observed upon the addition of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
1
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(37 citation statements)
references
References 22 publications
1
33
1
2
Order By: Relevance
“…2e). it is therefore likely that the molecule consists of 5 and not of 10 protomers. This is distinct from the decameric, "doublet" structures described for Clt and amyloid P-component, which tend in addition to form rod-like stacks of several molecules (12)(13)(14), but it is consistent with the molecular weights of rabbit CRP and its subunit, 118,000 (8) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2e). it is therefore likely that the molecule consists of 5 and not of 10 protomers. This is distinct from the decameric, "doublet" structures described for Clt and amyloid P-component, which tend in addition to form rod-like stacks of several molecules (12)(13)(14), but it is consistent with the molecular weights of rabbit CRP and its subunit, 118,000 (8) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, one of these agents, C-reactive protein (CRP), would appear to act in a manner entirely analogous to immunoglobulin. It has been found that upon interaction with a variety of substances, CRP can activate the C cascade and initiate both the opsonic and lytic potentials of this system through an activation of the primary C pathway (3)(4)(5)(6). CRP has been described as being comprised of probably identical subunits, ca 23,000 daltons, noncovalently linked to form an oligomer of molecular weight 120,000-140,000 (7,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CRP was initially defined by a unique, calcium-dependent precipitation reaction with the pneumococcal C-polysaccharide (1,2). In addition, CRP is an agglutinin (3) and an opsonin (4), and, in the presence of a suitable ligand, CRP activates the complement system to cause depletion of complement component hemolytic activity (5)(6)(7) and promotion of complement-dependent opsonization (8) and hemolysis (9). This array of properties, reminiscent of specific antibody, has prompted us to postulate shared functions and a common evolutionary origin for CRP and immunoglobulins.…”
mentioning
confidence: 99%